Facile patterning of amorphous indium oxide thin films based on a gel-like aqueous precursor for low-temperature, high performance thin-film transistors. Issue 10 (22nd February 2016) - Li, Yuzhi; Lan, Linfeng; Xiao, Peng; Lin, Zhenguo; Sun, Sheng; Song, Wei; Song, Erlong; Gao, Peixiong; Zhang, Peng; Peng, Junbiao
Abstract : Facile patterning of chloride-based precursor films for low-temperature, high performance indium oxide thin-film transistors. Abstract : A "green precursor" and a "green patterning technique" were used to fabricate low temperature processed indium oxide (InO x ) semiconductors. For the InO x precursor, chloride ligand-based indium(iii ) was dissolved in deionized (DI) water without any additives to form a gel-like precursor. The as-spin-coated precursor films could be facilely patterned using the "green patterning technique", which requires only ultraviolet (UV) irradiation and DI water. A systematic study was carried out to investigate the chemical reaction of the chloride-based precursor films as well as the semiconductor properties. It was found that UV irradiation and water treatment not only helped to transform In–Cl into In–OH, but also helped to remove the Cl-related impurities. It led to the activation of InO x films at temperatures as low as 180 °C. The mobility of InO x TFTs based on an anodized aluminium oxide (AlO x :Nd) insulator with patterning was improved by more than 1 order compared to that without patterning at an annealing temperature of 280 °C. In addition, flexible InO x TFTs on polyimide (PI) substrates were demonstrated. They showed only a little degradation in the subthreshold region of the transfer curve even at a bending curvature ( R ) of 5 mm.